Dampak Profitabilitas pada Pengaruh Leverage dan Likuiditas terhadap Ketepatan Waktu Penyampaian Laporan Keuangan selama Pandemi COVID-19 - Aqilah Syahidah; Rida Prihatni; Dwi Handarini (Jurnal Akuntansi dan Keuangan, 2023)
Companies with shares on public exchanges must present their financial reports in a timely manner. Some businesses did not take advantage of the government's easing of financial reporting requirements that was instituted in the wake of the Covid-19 outspread. The intention of this study is to experimentally enquire how profitability affects the connection between leverage, liquidity, and timely filing of financial statements. From 2019 through 2021, the research specialize on energy companies trading on the Indonesia Stock Exchange. A total of 177 data points were collected from 59 different businesses thanks to some strategic sampling. For these data, we ran a logistic regression followed by a test for a moderate regression analysis interaction. The upshot adduce that although liquidity has an effect on the timeliness of filing financial statements, leverage does not. Profitability also amplifies the impact of leverage and liquidity on meeting the deadline for submitting financial statements. Therefore, the upshot of this research adduce that not all debt ratios have an impact on timely financial reporting, and that profitability plays a critical role in amplifying the effect of leverage and liquidity on the timeliness of financial report submission